Behavioural plasticity under a changing climate; how an experimental local climate affects the nest construction of the zebra finch Taeniopygia guttata. (7th May 2018) - Campbell, Bridget L.; Hurley, Laura L.; Griffith, Simon C.
Abstract : Successful reproduction in most avian species is dependent on the construction of a nest that provides protection and a suitable microclimate for the eggs and developing nestlings. Observational studies suggest that climatic variation may affect the structure of the nest, but to date there have been no attempts to experimentally determine the role that local climate plays in the construction of a suitable nest. Using a within‐individual counter balanced design we investigated how nest composition and construction differ in zebra finches breeding in ambient conditions of 18°C and 30°C. We found that at 18°C birds built nests that were over 20% heavier, and with significantly more thread and less grass than those built at 30°C. Our results highlight the degree of plasticity in nest building behaviour in relation to local ambient conditions. These results suggest that nest building behaviour is one route through which birds can respond to a changing climate and modify the microclimate of their nest in line with projected changes in ambient conditions.